Genoprettende ret i det danske ungdomskriminalitetsnævn? - Barnekow Rasmussen, Katrine (Nordisk Tidsskrift for Kriminalvidenskab, 2023)
Abstract The Danish Youth Crime Boards were launched January 1, 2019. They were part of a new legislation to fight and prevent youth offending. The target group consists of offenders aged 10 to 17, of which those 10 to 14 are legally considered below the age of criminal responsibility. In the legislative framework it is recommended that the verdicts of the boards should have a ‘restorative character to the extent possible’. A new category of verdicts – instant reactions – is introduced in this context. It is noted in several places that these verdicts should be in line with the principles of restorative justice. In the current article, I examine this restorative aspect of the legislative framework of the boards, as well as how it is put into practice by the boards and perceived by board members. Not only does the legislative framework appear unclear on this aspect, it also does not seem to align with recognized international definitions of restorative justice, the principles of which the verdicts of the boards should be in line with. As of October 31, 2021, instant reactions had only been applied in 1.5% of the cases handled by the boards. A key reason for this is that the municipal recommendations – on the basis of which the boards issue their verdicts – do not include instant reactions in the vast majority of cases. Furthermore, the author’s survey among board members displays a notable uncertainty regarding appropriate instant reactions as well as rather varied connotations of how restorative character should be understood in this context. The Danish political level displays dissatisfaction with the limited usage of instant reactions to date. Initiatives are on the way to address this point, including a catalogue of ideas for possible instant reactions. The author questions whether this approach will actually take the practice of the boards in a more restorative direction. Instead, the author suggests looking towards Norway for inspiration on this matter.